2021
DOI: 10.1088/1748-0221/16/11/p11005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature anneal cycling on a cryogenically proton irradiated CCD

Abstract: Throughout a typical Earth orbit a satellite is constantly bombarded by radiation with trapped and solar protons being of particular concern as they gradually damage the focal plane devices throughout the mission and degrade their performance. To understand the impact the damage has on CCDs and how it varies with their thermal history a proton radiation campaign has been carried out using a CCD280. The CCD is irradiated at 153 K and gradually warmed to 188 K in 5 K increments with Fe55 X-ray, dark current and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…When comparing the three fitted emission time constants between the results for the in-flight and the on-ground data, it is noted that while the orders of magnitude are the same between the two datasets, the fitted values are not. Furthermore, the emission time constants in tables 1 and 2 do not match values of any real, physical traps when comparing the results with trap landscapes from other studies [7].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…When comparing the three fitted emission time constants between the results for the in-flight and the on-ground data, it is noted that while the orders of magnitude are the same between the two datasets, the fitted values are not. Furthermore, the emission time constants in tables 1 and 2 do not match values of any real, physical traps when comparing the results with trap landscapes from other studies [7].…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that the on-ground irradiations and subsequent radiation damage during the pre-flight tests were not reflective of radiation damage in space. For the case of Gaia, the on-ground irradiations were performed at room-temperature which are known to produce different trap landscapes as compared to cryogenic irradiations that are more reflective of in-flight conditions [7]. In order to compare the CTI measurements and the irradiation effects between in-flight and on-ground conditions, a new set of on-ground charge calibration data was obtained in the same format as the in-flight data, using a Gaia CCD91-72 flight-spare in the laboratory.…”
Section: Pyxelmentioning
confidence: 99%
“…The continuum is a group of trap defects with a large spread of emission time constants that are found between the divacancy and "unknown" peaks in previous studies of trap defect landscapes. 18 The continuum has been noted to be produced in larger densities following a cryogenic irradiation as compared to room-temperature irradiations due to being physically stable at low temperatures and annealing at high temperatures; it is likely to be responsible for some of the differences in CTI between the in-flight and on-ground data. 19 In order to model the most likely trap defect landscapes in the in-flight and on-ground datasets, C3TM CI simulations of the divacancy and "unknown" were generated and the charge tails were compared against corresponding charge tails from CDM CI simulations.…”
Section: Cdm and C3tm Comparisonsmentioning
confidence: 99%
“…As discussed previously from other studies, a greater proportion of continuum is obtained from cryogenic irradiations as opposed to roomtemperature irradiations. 18,19 This difference in continuum is most probably due to the different irradiation conditions between in-flight and on-ground, given the fact that the on-ground irradiations were performed at room-temperature. In fact, it has been found that the continuum causes the largest proportionate amount of CTI in Gaia as compared to the other defects.…”
Section: In-flight and On-ground Trap Landscapesmentioning
confidence: 99%
“…The dominant species is the trap with an emission time constant closest to the pumping phase delay times, which have been selected as they correspond to the expected readout speeds during the SMILE mission (at time of data being taken). At 153 K the Divacancy has a time constant of approximately 5x10 −4 s [8] which makes it the most efficiently pumped when using the conditions specified in table 2 and therefore the dominant trap species.…”
Section: Jinst 17 P10025mentioning
confidence: 99%